Route Optimization Based Waste Collection System Planning Using the Saving Matrix Approach at UPN “Veteran” East Javaptimization-Based Waste Collection System Using the Saving Matrix Approach at UPN “Veteran” East Java: Perencanaan Sistem Pengumpulan Sampah Berbasis Optimasi Rute dengan Pendekatan Saving Matrix UPN “Veteran” Jawa Timur - Fransisca Nanda Auliya; Praditya Sigit Ardisty Sitogasa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The waste collection system on campus has become a strategic challenge as the academic community continues to grow. This case study aims to analyze the characteristics of waste generation and optimize waste collection routes from building collection points to the Temporary Storage Site (TPS) at UPN “Veteran” East Java. The weight and volume of waste generated data were obtained through measurements taken over eight days in accordance with SNI (Standar Nasional Indonesia) standards. The Saving Matrix method was applied to develop optimal transportation routes to reduce the total daily distance traveled. The results of the study show that the total waste generated reached 11.525 m3/day. The implementation of the Saving Matrix method successfully improved operational efficiency significantly, with a 22,7% reduction in total daily travel distance compared to existing conditions. The results of this analysis provide a tangible contribution to campus facilities and infrastructure management in designing a waste transportation system that is more effective, measurable, and operationally efficient.